Employing a T-shirt template and variant of Schweizer's reagent for constructing a low-weight, flexible, hierarchically porous and textile-structured copper current collector for dendrite-suppressed Li metal. Issue 47 (22nd November 2019) - Zhu, Ruijie; Sheng, Nan; Rao, Zhonghao; Zhu, Chunyu; Aoki, Yoshitaka; Habazaki, Hiroki
Abstract : A low-weight and flexible T-shirt structured porous Cu current collector with superior performance for Li metal anodes was fabricated and could suppress Li dendrite growth. Abstract : The utilization of a Li metal anode is necessary in the development of next generation high energy density Li batteries, which is still hindered by problems of dendrite growth, volume change and electrolyte depletion. To overcome these difficulties, the employment of 3D porous current collectors has been demonstrated to be an effective strategy. However, the widely used porous metallic current collectors, such as commercial Cu foam, are always too heavy to meet the demand for high energy density. In this work, we develop a low-weight, flexible, hierarchically porous and textile-structured Cu current collector via a smart cotton T-shirt template method. By employing a variant of Schweizer's reagent as the Cu source, the T-shirt moulded Cu framework can inherit the textile morphology. The hierarchically porous structure and high surface area can lower the local current density, and the unique 3D structure can confine the growth of Li crystals, all of which can endow the novel textile-structured Cu with superior performance as a current collector for Li metal anodes. Furthermore, this strategy provides a convenient route for designing template-structured frameworks, which is useful not only for the development of a current collector, but also for the preparation of numerous structure-oriented materials.